From the Skin: Defending Indigenous Nations Using Theory and Praxis - Estes, Nick; Boxer, Elise; Clark, Jerome Jeffery (Critical Issues in Indigenous Studies, 2023)
In this volume, contributors demonstrate the real-world application of Indigenous theory to the work they do in their own communities and how this work is driven by urgency, responsibility, and justice-work that is from the skin . In From the Skin , contributors reflect on and describe how they apply the theories and concepts of Indigenous studies to their communities, programs, and organizations, and the ways the discipline has informed and influenced the same. They show the ways these efforts advance disciplinary theories, methodologies, and praxes. Chapters cover topics including librarianship, health programs, community organizing, knowledge recovery, youth programming, and gendered violence. Through their examples, the contributors show how they negotiate their peoples' knowledge systems with knowledge produced in Indigenous studies programs, demonstrating how they understand the relationship between their people, their nations, and academia. Editors J. Jeffery Clark and Elise Boxer propose and develop the term practitioner-theorist to describe how the contributors theorize and practice knowledge within and between their nations and academia. Because they live and exist in their community, these practitioner-theorists always consider how their thinking and actions benefit their people and nations. The practitioner-theorists of this volume envision and labor toward decolonial futures where Indigenous peoples and nations exist on their own terms. Contributors Randi Lynn Boucher-Giago Elise Boxer Shawn Brigman J. Jeffery Clark Nick Estes Eric Hardy Shalene Joseph Jennifer Marley Brittani R. Orona Alexander Soto